2017
DOI: 10.1016/j.expneurol.2017.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Genetic neutrophil deficiency ameliorates cerebral ischemia-reperfusion injury

Abstract: Neutrophils respond rapidly to cerebral ischemia and are thought to contribute to inflammation-mediated injury during stroke. Using myeloid Mcl1 knockout mice as a model of genetic neutrophil deficiency, we investigated the contribution of neutrophils to stroke pathophysiology. Myeloid Mcl1 knockout mice were subjected to transient middle cerebral artery occlusion and infarct size was assessed by MRI after 24 hours reperfusion. Immune cell mobilization and infiltration was assessed by flow cytometry. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…We predicted the possible messenger RNA (mRNA) targets of miR-34b-3p using starBase database. EPHA4, 15 MCL1, 21 PDE4D, 22 BCL2L13, 23 GATA3 24 and ROCK1 25 were chosen due to their important regulatory functions in cerebral ischemia-reperfusion injury. EPHA4 was chosen for further analysis due to its the most significant negative regulatory relationship with miR-34b-3p ( Supplementary Figure 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…We predicted the possible messenger RNA (mRNA) targets of miR-34b-3p using starBase database. EPHA4, 15 MCL1, 21 PDE4D, 22 BCL2L13, 23 GATA3 24 and ROCK1 25 were chosen due to their important regulatory functions in cerebral ischemia-reperfusion injury. EPHA4 was chosen for further analysis due to its the most significant negative regulatory relationship with miR-34b-3p ( Supplementary Figure 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…147 The lung as a site of neutrophil priming Because CA induces both systemic ischemia and inflammation, neutrophils are primed in the periphery long before reaching the CNS. 148 Yet, while genetic models of neutrophil deficiency support their role in exacerbating cerebral reperfusion injury, 149 anti-neutrophil strategies have failed in clinical trials for acute cerebral ischemia. 150 This apparent contradiction may reflect the fact that like microglia, neutrophils are also capable of adopting either pro-(N1) or anti-(N2) inflammatory phenotypes.…”
Section: The Lung: Immuno-homeostatic Mechanismsmentioning
confidence: 99%
“…This is likely due, in large part, to the fact that many of the targeted molecules are not neutrophil-specific, leading to a high degree of nonspecificity. Interestingly, a recent study found that specific genetic deletion of neutrophils (Mcl1 knockout) did not improve neurological deficits after ischemic stroke in mice [25]. However, it is critically important to note that the Mcl1 study, and all previous anti-neutrophil therapies in acute ischemic stroke, were performed only in young animals.…”
Section: Discussionmentioning
confidence: 99%